Shuffle-Sum: Coercion-Resistant Verifiable Tallying for STV Voting - Benaloh, Josh; Moran, Tal; Naish, Lee; Ramchen, Kim; Teague, Vanessa (Transactions on Information Forensics and Security, 2009)
There are many advantages to voting schemes in which voters rank all candidates in order, rather than just choosing their favourite. However, these schemes inherently suffer from a coercion problem when there are many candidates, because a coercer can demand a certain permutation from a voter and then check whether that permutation appears during tallying. Recently developed cryptographic voting protocols allow anyone to audit an election (universal verifiability), but existing systems are either not applicable to ranked voting at all, or reveal enough information about the ballots to make voter coercion possible. We solve this problem for the popular single transferable vote (STV) ranked voting system, by constructing an algorithm for the verifiable tallying of encrypted votes. Our construction improves upon existing work because it extends to multiple-seat STV and reveals less information than other schemes. The protocol is based on verifiable shuffling of homomorphic encryptions, a wellstudied primitive in the voting arena. Our protocol is efficient enough to be practical, even for a large election.